Vipegitide: a folded peptidomimetic partial antagonist of α2β1 integrin with antiplatelet aggregation activity - Momic T; Katzhendler J; Shai E; Noy E; Senderowitz H; Eble JA; Marcinkiewicz C; Varon D; Lazarovici P (Dove Medical Press, 2015)
Tatjana Momic,1 Jehoshua Katzhendler,1 Ela Shai,2 Efrat Noy,3 Hanoch Senderowitz,3 Johannes A Eble,4 Cezary Marcinkiewicz,5 David Varon,2 Philip Lazarovici11School of Pharmacy Institute for Drug Research, Faculty of Medicine, The Hebrew University of Jerusalem, 2Department of Hematology, Coagulation Unit, Hadassah-Hebrew University Medical Center, Jerusalem, Israel; 3Department of Chemistry, Bar-Ilan University, Ramat-Gan, Israel; 4Institute for Physiological Chemistry and Pathobiochemistry, University of Münster, Münster, Germany; 5Department of Bioengineering, College of Engineering, Temple University, Philadelphia, PA, USAAbstract: Linear peptides containing the sequence WKTSRTSHY were used as lead compounds to synthesize a novel peptidomimetic antagonist of α2β1 integrin, with platelet aggregation-inhibiting activity, named Vipegitide. Vipegitide is a 13-amino acid, folded peptidomimetic molecule, containing two α-aminoisobutyric acid residues at positions 6 and 8 and not stable in human serum. Substitution of glycine and tryptophan residues at positions 1 and 2, respectively, with a unit of two polyethylene glycol (PEG) molecules yielded peptidomimetic Vipegitide-PEG2, stable in human serum for over 3 hours. Vipegitide and Vipegitide-PEG2 showed high potency (7×10-10 M and 1.5×10-10 M, respectively) and intermediate efficacy (40% and 35%, respectively) as well as selectivity toward α2 integrin in inhibition of adhesion of α1/α2 integrin overexpressing cells toward respective collagens. Interaction of both peptidomimetics with extracellular active domain of α2 integrin was confirmed in cell-free binding assay with recombinant α2 A-domain. Integrin α2β1 receptor is found on the platelet membrane and triggers collagen-induced platelet aggregation. Vipegitide and Vipegitide-PEG2 inhibited α2β1 integrin-mediated adhesion of human and murine platelets under the flow condition, by 50%. They efficiently blocked adenosine diphosphate- and collagen I-induced platelet aggregation in platelet rich plasma and whole human blood. Higher potency of Vipegitide than Vipegitide-PEG2 is consistent with results of computer modeling of the molecules in water. These peptidomimetic molecules were acutely tolerated in mice upon intravenous bolus injection of 50 mg/kg. These results underline the potency of Vipegitide and Vipegitide-PEG2 molecules as platelet aggregation-inhibiting drug lead compounds in antithrombotic therapy.Keywords: adhesion, collagen I, platelets, integrin antagonist, peptidomimetic